Auxin-induced SCF(TIR1)–Aux/IAA interaction involves stable modification of the SCF(TIR1) complex - Kepinski, Stefan (National Academy of Sciences, 2004)
The plant hormone auxin can regulate gene expression by destabilizing members of the Aux/IAA family of transcriptional repressors. Auxin-induced Aux/IAA degradation requires the protein-ubiquitin ligase SCF(TIR1), with auxin acting to enhance the interaction between the Aux/IAAs and SCF(TIR1). SKP1, Cullin, and an F-box-containing protein (SCF)-mediated degradation is an important component of many eukaryotic signaling pathways. In all known cases to date, the interaction between the targets and their cognate SCFs is regulated by signal-induced modification of the target. The mechanism by which auxin promotes the interaction between SCF(TIR1) and Aux/IAAs is not understood, but current hypotheses propose auxin-induced phosphorylation, hydroxylation, or proline isomerization of the Aux/IAAs. We found no evidence to support these hypotheses or indeed that auxin induces any stable modification of Aux/IAAs to increase their affinity for SCF(TIR1). Instead, we present data suggesting that auxin promotes the SCF(TIR1)–Aux/IAA interaction by affecting the SCF component, TIR1, or proteins tightly associated with it.